PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP NILAI PERUSAHAAN (Media Riset Akuntansi, 2022)
The purpose of this study was to determine and analyze the effect of good corporate governance structure and firm ownership on firm value. The population of this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2014-2017. The sampling technique used is the purposive sampling method. The number of samples in this study were 108 samples. This study uses a descriptive analysis method using the SPSS 23 program. Based on the results of hypothesis testing, it shows that independent commissioners, institutional ownership, and the board of directors have a significant influence on firm value. Meanwhile, managerial ownership and audit committee have no effect on firm value. The results of this study are expected to contribute to the field of financial accounting.